Effects of Ta substitution and addition of nano-MgO particles on formation and superconductivity of TlSr1212 ceramics / Zulzamri Salleh - Salleh, Zulzamri (2008)
In this work, the effect of tantalum (Ta) substitutions at the Sr-site on superconductivity of Tl0.9Bi0.1Sr2-xTaxCa0.9Y0.1Cu2O7 (x = 0 - 0.40) series and the effect of nanosize MgO particles on 1212 phase formation and transport critical current density, Jc in external magnetic field for Tl0.9Bi0.1Sr1.95Ta0.05Ca0.9Y0.1Cu2O7 + yMgO (y = 0 - 0.8 wt.%) series and Tl0.5Pb0.5Sr1.8Yb0.2CaCu2O7 + zMgO (z = 0 - 0.80 wt.%) series superconductors were investigated. Results of tantalum substitution at Sr-site in Tl0.9Bi0.1Sr2-xTaxCa0.9Y0.1Cu2O7 (x = 0 - 0.40) series showed that the best superconducting behavior occurred at x = 0.05 with Tconset of 96 K and Tczero of 65 K. Higher Ta substitution caused gradual deterioration of superconductivity, accompanied by a change of normal state behavior from metallic to semiconductor-like behavior with increasing Ta. SEM investigation showed changes in grain size with Ta substitution. Results of electrical measurements on Tl0.9Bi0.1Sr1.95Ta0.05Ca0.9Y0.1Cu2O7 + yMgO (y = 0 - 0.8 wt.%) series superconductor revealed the highest transport critical current density Jc (at 20 K) of28 A/cm2 at y = 0.2 wt.%. Samples withy = 0 - 0.40 wt.% showed a rapid drop of Jc at low fields (< 0.1 Tesla) before a slower deterioration at higher fields (> 0.1 Tesla). This indicates the presence of weak links at low fields and dominance of strong links at higher fields. The smallest drop of Jc was observed for sample y = 0.2 wt.%. SEM results for these series showed no significant difference in microstructure between MgO added samples. Results of electrical measurements on Tl0.5Pb0.5Sr1.8Yb0.2CaCu2O7 + zMgO (z = 0 - 0.80 wt.%) series revealed the highest Jc (at 30 K) of 16 A/cm2 for z = 0.1 wt.%. The behavior of Jc in external fields also indicates presence of weak links at low fields. The smallest drop of Jc was observed for z = 0.1 wt.%. SEM micrographs of MgO added samples showed smaller grain size compared to pure samples. The enhanced Jc at y = 0.2 wt.% for the Tl0.9Bi0.1Sr1.9Ta0.05Ca0.9Y0.1Cu2O7 +yMgO series and z = 0.1 wt.% for the Tl0.5Pb0.5Sr1.8Yb0.2CaCu2O7 + zMgO series is suggested to be due to flux pinning as a result of the MgO additions. In conclusion, substitution of Ta0.05 at Sr-site successfully stabilized the 1212-phase during synthesis of T11212 superconductors. The addition of a moderate amount of nano-MgO particle before final sintering improved transport critical current density and enhanced flux pinning ability of the Tl-1212 superconductors.